Discovery of survival factor for primitive chronic myeloid leukemia cells using induced pluripotent stem cells - Kran Suknuntha; Yuki Ishii; Lihong Tao; Kejin Hu; Brian E. McIntosh; David Yang; Scott Swanson; Ron Stewart; Jean Y.J. Wang; James Thomson; Igor Slukvin (Stem Cell Research, 2015)
A definitive cure for chronic myeloid leukemia (CML) requires identifying novel therapeutic targets to eradicate leukemia stem cells (LSCs). However, the rarity of LSCs within the primitive hematopoietic cell compartment remains a major limiting factor for their study in humans. Here we show that primitive hematopoietic cells with typical LSC features, including adhesion defect, increased long-term survival and proliferation, and innate resistance to tyrosine kinase inhibitor (TKI) imatinib, can be generated de novo from reprogrammed primary CML cells. Using CML iPSC-derived primitive leukemia cells, we discovered olfactomedin 4 (OLFM4) as a novel factor that contributes to survival and growth of somatic lin−CD34+ cells from bone marrow of patients with CML in chronic phase, but not primitive hematopoietic cells from normal bone marrow. Overall, this study shows the feasibility and advantages of using reprogramming technology to develop strategies for targeting primitive leukemia cells.